2014
DOI: 10.1186/1478-811x-12-16
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 and IL-27 regulate the phagolysosomal pathway in mycobacteria-infected human macrophages

Abstract: BackgroundThe cytokine environment at the site of infection is important to the control of mycobacteria by host macrophages. During chronic infection immunosuppressive cytokines are likely to favor mycobacterial growth, persistence, and an avoidance of proper antigen processing and presentation. The activity of interleukin (IL)-27 toward macrophages is anti-inflammatory and this compromises control of mycobacteria. Modulation of the cytokine environment may enhance both protective and vaccine-induced responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 40 publications
4
83
2
Order By: Relevance
“…63,64 IL-27 also confers immunosuppressive properties to several immune cells. Although the anti-inflammatory role of IL-27 has been reported during the course of inflammation, 52,65 knowledge is limited about its role during the regulation of myeloid cell polarization and in the regulation of innate immunity. IHC analysis of ovarian cancer tissues revealed that tumor-infiltrating neutrophils represent the main source of IL-27.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 IL-27 also confers immunosuppressive properties to several immune cells. Although the anti-inflammatory role of IL-27 has been reported during the course of inflammation, 52,65 knowledge is limited about its role during the regulation of myeloid cell polarization and in the regulation of innate immunity. IHC analysis of ovarian cancer tissues revealed that tumor-infiltrating neutrophils represent the main source of IL-27.…”
Section: Discussionmentioning
confidence: 99%
“…12 It is believed 16,[39][40] Previous studies also emphasized on the role of IL-27 in bacterial infections. 41 Jung and associates showed the role of IL-27 and also STAT-3 on lysosomal activity, which finally renders to enhanced trafficking of mycobacteria toward lysosomes in human macrophages. 41 The role of IL-27 in the pathogenesis of other viral infections show its prominent role in removing viruses, for example; study of the role of IL-27 in influenza virus type A replication and gene expression showed inhibition and antiviral function of IL-27 which enforced by activation of STAT1/2/3.…”
Section: Discussionmentioning
confidence: 99%
“…41 Jung and associates showed the role of IL-27 and also STAT-3 on lysosomal activity, which finally renders to enhanced trafficking of mycobacteria toward lysosomes in human macrophages. 41 The role of IL-27 in the pathogenesis of other viral infections show its prominent role in removing viruses, for example; study of the role of IL-27 in influenza virus type A replication and gene expression showed inhibition and antiviral function of IL-27 which enforced by activation of STAT1/2/3. 42 Wang and associates carried out a gene expression profiling study and found that IL-27 serum levels were significantly higher in HBV-infected patients in comparing with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…This alkaline pH hinders the transport of material from early endosomes to late endosomes arresting the phagosome maturation [29]. In human macrophages Jung and Robinson [30] have shown that infected macrophages express the P28 and the Epstein-Barr virus induced gene s (EBI3) proteins and the cell secretes the active IL-27. The IL-27 then engages its receptor on the same cell and down regulates the expression of the v-ATPase.…”
Section: Mechanisms Used By Mycobacteria To Evade Immune System and Smentioning
confidence: 99%